Small molecule inhibitors of Aurora-A induce proteasomal degradation of N-Myc in childhood neuroblastoma - Brockmann, Markus; Poon, Evon; Berry, Teeara; Carstensen, Anne; Deubzer, Hedwig; Rycak, Lukas; Jamin, Yann; Thway, Khin; Robinson, Simon P.; Roels, Frederik; Witt, Olaf; Fischer, Matthias; et al. (Cancer cell, 2013)
Amplification of MYCN is a driver mutation in a subset of human neuroendocrine tumors, including neuroblastoma. No small molecules that target N-Myc, the protein encoded by MYCN, are clinically available. N-Myc forms a complex with the Aurora-A kinase, which protects N-Myc from proteasomal degradation. Although stabilization of N-Myc does not require the catalytic activity of Aurora-A, we show here that two Aurora-A inhibitors, MLN8054 and MLN8237, disrupt the Aurora-A/N-Myc complex and promote degradation of N-Myc mediated by the Fbxw7 ubiquitin ligase. Disruption of the Aurora-A/N-Myc complex inhibits N-Myc-dependent transcription, correlating with tumor regression and prolonged survival in a mouse model of MYCN-driven neuroblastoma. We conclude that Aurora-A is an accessible target that makes destabilization of N-Myc a viable therapeutic strategy.
Gesehen am 08.12.2020